Marginal fan thick lacustrine sedimentation: Implication for tectonics and/or climatic causes in Kathmandu basin - Paudel, Mukunda Raj (Journal of Nepal Geological Society, 2022)
Very thick gravel deposits are widely distributed from southern marginal to central parts of the Kathmandu basin named as Itaiti Formation. This deposit is more than 120 m thick and deposited around 1 Ma, which is dominated by three types of facies and fans. The first stage fan is widely distributed near the mountain front where sediments aggradation is more active. The third stage fan is the youngest among three fans and is distributed on the present top surface and has covered lacustrine deltaic sequence of the Sunakothi Formation. Seven types of facies elements namely Gms, Gm, Gp, Sp, Sr, Sh, and Fl have been recognized among these three fans. Based on stratigraphic relationship among different geological formations, the first debris flow fans have been spreading over basement rocks and fluvial gravel facies before 1 Ma. This event has played a vital role in the initiation of an ancient lake in the Kathmandu basin. The second and third stage fans originated during the draining stages of the lake. The distal part of the second stage fan and third stage fan is interfingering with the lacustrine delta towards the center of the basin. The first stage debris flow fan was most probably generated by the recent uplift of the Mahabharat range. These gravelly fan deposits and the uppermost Siwalik conglomerate deposits may be synchronous to recent tectonic events throughout the Himalayas. The second and third stage fans have been initiated not only by the tectonics but also by climatic which is indicated by sedimentological and stratigraphic relations among formations.